Incidence of Pathologies Associated with Impacted Mandibular Premolars and Third Molars - Yandeti Srinivasulu1 , Abdul Wahab2 , Senthil Murugan.P3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Impaction is the cessation of eruption or failure of a tooth to erupt caused by a physical barrier in theeruption path, abnormal positioning of tooth and loss of space are other impediments.The rising incidenceof impacted teeth and their influence on the dental arches have long been of concern to the oral maxillofacialsurgeons.The aim of the study is to evaluate different types of Mandibular pathologies associated withimpacted third molars. This was a retrospective study conducted in the Department of Oral and MaxillofacialSurgery in Saveetha Dental College, Chennai . A total of 470 cases ranging in the age from 18 years to 45years with the diagnosis of Impacted mandibular third molars were considered for this study. Data wereanalysed using IBM SPSS statistics.This study showed vertical impaction and mesioangular impaction weremost frequently involved in the formation of cystic lesions among which vertical impaction occupied (1.7%)and mesioangular impaction (0.2%).Tumors with 0.6% are associated with vertical impaction of mandibularthird molar followed by mesioangular and distoangular impactions.Within the limitation of the study,weobserved that there exists a significant incidence of Pathologies associated with impacted mandibular thirdmolars .